Diarrheagenic Escherichia coli and Acute Gastroenteritis in Children in Davidson County, Tennessee, United States: A Case-control Study. Issue 6 (June 2018) - Imdad, Aamer; Foster, Monique A.; Iqbal, Junaid; Fonnesbeck, Christopher; Payne, Daniel C.; Zhang, Chengxian; Chappell, James D.; Halasa, Natasha; Gómez-Duarte, Oscar G.
Abstract : Background: Diarrheagenic Escherichia coli (DEC) is an important cause of acute gastroenteritis in children; however, there is limited information available on the epidemiology, phylogenetics, serotyping and antibiotic susceptibility of DEC in children in the United States. The aim of this study was to determine the molecular epidemiology of DEC among children with and without acute gastroenteritis in Davidson County, Tennessee. Methods: This prospective, frequency matched, case-control study recruited subjects 15 days to 17 years of age and detected DEC with polymerase chain reaction from stool samples. Additional testing was done to define phylogenetics and antibiotics resistance. Results: Among 1267 participants, 857 cases and 410 controls, 5.5% were positive for at least one subtype of DEC. Enteroaggregative E. coli [n = 32 (45%)] was the most common subtype followed by enteropathogenic E. coli (EPEC) [n = 30 (43%)], Shiga toxin-producing E. coli [n = 4 (6%)] and diffusely adherent E. coli [n = 4 (6%)]. No significant difference in prevalence of DEC was found between cases (5%) and controls (7%) [odds ratio: 0.66 (95% confidence interval: 0.4–1.07)], and results were similar when data were stratified by subtypes and adjusted for age, sex, race and ethnicity. Substantial diversity was found among DEC isolates in terms of phylotypes and serotypes, and a large proportion was resistant to, at least, one antibiotic. Conclusions: Enteroaggregative E. coli and enteropathogenic E. coli were frequently found in both cases and controls in this study population. DNA-based methods for detection of these subtypes need further investigation to help differentiate between pathogenic and colonizing strains. Abstract : Supplemental Digital Content is available in the text.